Age-related language performance and device use in children with very early bilateral cochlear implantation - Glaubitz, Cynthia; Liebscher, Tim; Hoppe, Ulrich (International Journal of Pediatric Otorhinolaryngology, 2021)
Objectives: Paediatric cochlear implantation within the first year of life results in better outcome in auditory and language skills. Beside individual, audiological and social factors, quantity and quality of daily cochlear implant (CI) use also seem to be an influencing factor. The purpose of this study was to evaluate children's early receptive and expressive language performance considering bilingual language development as well as quantity and quality of daily CI use and intraoperative objective measurements. Methods: The retrospective analysis included data from 35 very early bilaterally cochlear-implanted children (age at CI M = 8.4 +/- 1.5 months). Language performance was assessed by the German standardised test SETK-2 (age at testing M = 29.4 +/- 4.0 months). The CI system-integrated data-logging was analysed with regard to daily CoilOn-time, CoilOff and exposure to classified listening scenes. Intraoperatively measured thresholds of evoked compound action potentials (T-ECAPs) were analysed to ensure CI functionality. Results: The cohort showed language performance within the normal range for word comprehension, sentence comprehension and word production, level of sentence production was reduced. Overall, bilingual children performed less well than monolingual children. Intraoperative T-ECAPs were recorded for the total cohort and no anomalies were detected. Children used their CI for about 8.7 +/- 1.4 h per day, most of this time spent in a quiet environment (38%). Word production was significantly correlated with the daily duration of CI use (CoilOn-time) and with exposure to the listening environment Speech. No correlation was found between number of daily coil disconnections (CoilOff) and language performance. Conclusion: Very early bilateral cochlear implantation may result in age-appropriate language skills already at the age of 2 years. Monolingualism seems to a better condition for early language development with CI than bilingualism. Especially for word production, the daily duration of CI use and exposure time in a speechcharacterised environment seem to be additional positive factors. Monitoring the data-logs should be one important focus of professionals during the postoperative rehabilitation process to detect potential benefits and risks. These findings should be integrated into rehabilitative therapy and parent counselling.
CRIS-Team WoS Importer:2021-07-30